2019
DOI: 10.11606/s1518-8787.2019053001135
|View full text |Cite
|
Sign up to set email alerts
|

Health Survey in a Peruvian health system (ENSSA)

Abstract: OBJECTIVE: To report the design, methodology and initial results of the National Socioeconomic Survey of Access to Health of the EsSalud Insured. RESULTS: There were interviews in 25,000 homes, surveying 79,874 people, of which 62,659 were affiliated to EsSalud. The insured people are mainly males (50.6%) with a higher technical education level (39.7%). The insured population has mostly independent (95.0%) and own (68.1%) home. Only 34.5% of the insured practice some sport or physical exercise; 14.0% of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…En cada hogar seleccionado, todos los miembros asegurados a EsSalud fueron invitados a participar del estudio. El artículo de Llanos et al [28] ofrece detalles metodológicos del estudio primario. Para el presente análisis secundario, se incluyó a los individuos con edad ≥ 60 años y asegurados a EsSalud.…”
Section: Población De Estudiounclassified
“…En cada hogar seleccionado, todos los miembros asegurados a EsSalud fueron invitados a participar del estudio. El artículo de Llanos et al [28] ofrece detalles metodológicos del estudio primario. Para el presente análisis secundario, se incluyó a los individuos con edad ≥ 60 años y asegurados a EsSalud.…”
Section: Población De Estudiounclassified
“…However, the Peruvian Health System (PHS) has serious difficulties in providing health coverage to the indigenous population. A recent study found that only 64.8% of the rainforest population received medical care compared to 73.1% in the general population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to understand how the indigenous population who live in the Central Jungle of the Peruvian Amazon use their traditional therapies as well as the official health resources to overcome their health problems. It is important to highlight that the Peruvian government does not separate data by ethnicity and, for this reason, little is known about the population living in the rainforest [ 13 ]. This is a potential problem, since the rates of health problems and infectious diseases are not reliable [ 16 ], making this population overlooked in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…Among people between 45 and 59 years old, osteoarthritis was the second biggest cause of disability, with 109,804 DALYs, and in people above 60 years old represented 7% of total DALYs 7 – 9 . Without knowing the impact of osteoarthritis on people's lives, it is difficult to propose solutions, invest resources for prevention, and mitigate disability, especially among elders, who constitute a large group within the Peruvian social health insurance system (EsSalud), which cares for approximately 37% of people who seek medical attention 10 , 11 . Hence, there is an important need to estimate the burden of disease produced by osteoarthritis in this healthcare subsystem 11 .…”
Section: Introductionmentioning
confidence: 99%